A clinical case of a 21-year-old patient with idiopathic acute exudative pericarditis - Wołowiec, Łukasz; Rogowicz, Daniel; Bujak, Robert; Choma, Anna; Jaśniak, Albert; Osiak, Joanna; Wołowiec, Anna; Grześk, Grzegorz; Zukow, Walery (Journal of Education, Health and Sport, 2023)
act Pericarditis is a disease entity associated with the primary or secondary inflammation of its layers, which may be accompanied by the accumulation of fluid in the pericardial sac, the consequences of which depend mainly on the speed of its accumulation. The causes of pericardial diseases can be divided into infectious or non-infectious diseases, but in about 30% of cases the etiology of the disease cannot be determined. Pericarditis causes 5% of all emergency department visits related to non-ischemic chest pain. In the study we presented a case of a 21-year-old Caucasian male with acute exudative pericarditis, which required drainage of the pericardial sac despite the use of pharmacological treatment. The patient underwent a wide range of diagnostic tests and specialist consultations, but ultimately the etiological factor of acute exudative pericarditis could not have been identified. The therapy of acute exudative pericarditis, especially in the case of undetermined etiology, requires an individualized approach from the attending physician. Based on the observation of inflammatory parameters, imaging tests and clinical picture, the physician is to decide whether pericardiocentesis or modification of pharmacological treatment is necessary. Searching for the etiological factor is essential if it has an impact on the successive methods of diagnosis and treatment, especially in patients with recurrent idiopathic pericarditis or in the absence of a response to the therapy.